Neuroprotective activities of acai berries (Euterpe sp.): A review - Maryam N. ALNasser; Ian R. Mellor (Shahrekord University of Medical Sciences, 2022)
Dietary interventions rich in fruits and vegetables in aging people can reverse or mitigate age-related cognitive declines, delay the onset of neurodegenerative diseases (NDDs), and provide long-term health dividends. The novel food, popularly known as "Acai", is a berry belonging to the Euterpe genus of tropical palms trees and natively found in South America. Euterpe oleracea has been given much attention among scientists due to its high antioxidant capacity compared to other fruits and berries. Additionally, acai pulp composition analysis found that it contains various biologically active phytochemicals. In this review, we focused on current evidence relating to acai berry neuroprotection mechanisms and its efficacy in preventing or reversing neurodegeneration and age-related cognitive decline. A number of studies have illustrated the potential neuroprotective properties of acai berries. They have shown that their chemical extracts have antioxidant and anti-inflammatory properties and maintain proteins, calcium homeostasis, and mitochondrial function. Moreover, acai berry extract offers other neuromodulatory mechanisms, including anticonvulsant, antidepressant, and anti-aging properties. This neuromodulation gives valuable insights into the acai pulp and its considerable pharmacological potential on critical brain areas involved in memory and cognition. The isolated chemical matrix of acai berries could be a new substitute in research for NDD medicine development. However, due to the limited number of investigations, there is a need for further efforts to establish studies that enable progressing to clinical trials to consequently prove and ratify the therapeutic potential of this berry for several incurable NDDs.